Дополнения к описанию Moritzoppia keilbachi и описание нового рода Tetroppia (Acari, Oribatida) - Гордеева, Е.В. (Вестник зоологии, 1999)
Описание Moritzoppia keilbachi (Moritz, 1969) и диагноз рода Moritzoppia Subias et Rodriguez, 1986 дополнены данными о хетотаксии ног и морфологии дорсосеюгального района. Из видов, для которых есть информация о хетоме ног, только M. keilbachi может быть отнесена к этому роду. Описан новый род Tetroppia gen. n. (типовой вид Oppia clavigera Hammer, 1952). В состав рода включены 10 видов, описанные ранее из Сибири как виды рода Moritziella. The description of the Moritzoppia keilbachi (Moritz, 1969) and the definition of the genus Moritzoppia Subias et Rodriguez, 1986 are added by new data of the chaetom of legs and the morphology of the dorso-sejugal region. Only M. keilbachi can be included in this genus from species, for which the information about the leg chaetom is examined. New genus Tetroppia gen. n. (type species Oppia clavigera Hammer, 1952) is described. Ten species, described from Siberia in the genus Moritziella, are included in new genus Tetroppia gen. n: